Biodeterioration of Ancient Monument (Devarbija) of Chhattisgarh by Fungi - Lanjewar2, Kavita Sharma1*; Sandhya (Journal of Phytology, 2010)
Chhattisgarh is the land of ancient culture which has lots of ancient monuments, temples and fort. Every nook and corner of Chhattisgarh has traditional heritage. Numerous factors affect the stone durability. Stone surfaces are conti- nuously exposed to physical, chemical and biological degradation. Physical, chemical, and biological agents act in co-association, ranging from synergistic to antagonistic, to the deterioration. Among biological agents miroorganisms have critical importance, in stone deterioration. They can cause various damages on the stone surface. Biodeterioration processes result from complex interactions of surface-invading microbes with each other as well as with the surface material. Fungal ability in production of pigments and organic acids have crucial role in discoloration and degradation of monuments. Air acts as a vehicle for the dispersion of microorganisms. It introduces into air from different sources i.e. soil, water, organic waste of man, plant leaves, sneezes and cough. This investigation focuses on mycological survey of The Sita Devi Temple of Devarbija,Durg,Chhattisgarh. The 15 fungal floras were isolated. Aspergillus, Penicillium, Curvularia, Cladosporium, Fusarium, Mucor, Rhizopus, were dominant. During present study 88 fungal colonies were observed. Key words: Biodegradation, Devarbija, Fungi <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Dr Kavita Sharma and Sandhya Lanjewar. Biodeterioration of Ancient Monument (Devarbija) of Chhattisgarh by Fungi. J Phytol 2/11 (2010) 47-49